Tendon split lengthening technique for flexor hallucis longus tendon rupture - Jae Yong Park; Chenyu Wang; Hee Dong Kim; Hyong Nyun Kim (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Flexor hallucis longus (FHL) tendon rupture is a challenging injury to lead with clawing of the great toe when the FHL tendon is repaired too tight. When the diagnosis is delayed, the tendon ends may not be opposable because of contracture or poor tendon tissue. Methods A technique to reconstruct FHL tendon rupture without a free tendon graft is described. A split tendon lengthening is performed at the midfoot around the knot of Henry. Ankle block anesthesia is used to allow the patient’s active movement of the interphalangeal (IP) joint to determine the appropriate length of the reconstructed tendon for maintaining balance and preventing the tendon from being too tight or too loose. Between May 2012 and September 2015, five patients with a total rupture of the FHL tendon, having tendon defect distal to the knot of Henry, were treated with split tendon lengthening. Results Four patients could actively plantarflex the great toe IP joint. One patient who was operated under spinal anesthesia could not actively plantarflex the great toe IP joint, but did not have extension deformity and did not want another procedure. The mean American Orthopedic Foot and Ankle Society (AOFAS) score at a mean follow-up of 44 months was 92 points (range, 80–100). Conclusions This technique is described to overcome the difficulty of reconstructing the FHL tendon with tendon defect. The tendon defect could be repaired after split tendon lengthening without a free tendon graft.